Assessing policymaker and taxpayer attitudes towards public finance for urban sanitation: the case of sanitation surcharges in two Ghanaian municipalities. Issue 1 (2nd January 2021) - Oduro, Charles Y.; Appiah-Effah, Eugene; Nyarko, Kwabena B.
ABSTRACT: Municipal Authorities (Assemblies) in Ghana have been unable to generate adequate revenue to effectively manage sanitation. To address this challenge, the Akuapem North and Ga West Municipalities have recently introduced a sanitation surcharge, which is collected through property rates. Using a mixed-method approach, this paper assesses the attitudes of policymakers and taxpayers towards the policy and the implications for its effective implementation. Qualitative data were collected through interviews with officials of the Municipal Assemblies while quantitative data were collected through a survey of 832 randomly selected property owners. The study revealed that policymakers' de jure acceptance of the policy has not translated into de facto implementation. Although most taxpayers support the policy, a significant minority of them oppose it due to lack of trust in the Assemblies. Therefore, the Assemblies need to devise effective communication strategies, and enhance transparency in the use of revenue collected through the surcharge.